Analisis Kesulitan Calon Guru MI dan SD di Kabupaten Tanah Datar dalam Pengembangan Media Pembelajaran Berbasis Digital - Ana Nurul Falah; Adila Syafitri; Ananda Zahara Syahrani; Safrizal Safrizal (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2023)
This study aims to describe the difficulties of prospective MI/SD teachers in Tanah Datar District in developing digital-based learning media. This study uses a quantitative method with a descriptive approach. The subjects in this study were prospective MI/SD teachers in Tanah Datar District using a simple random sampling technique. The research instrument used was in the form of questions contained in Google Forms, with 5 questions answered by 163 prospective MI/SD teachers in Tanah Datar District. Data were analyzed using descriptive statistics. The research findings obtained indicate that prospective MI/SD teachers experience difficulties in developing digital-based learning media with several causes including 1) the low understanding of prospective MI/SD teachers in developing digital-based media is due to the lack of training regarding the development of digital-based learning media 2) prospective MI/SD teachers have difficulty studying material which tends to be long to be loaded into digital-based learning media and 3) time constraints in media development.